Case report: Human seminal plasma allergy diagnosis for a woman with unexplained infertility - Didziokaite, Gabija; Kuznecovaite, Aida; Biliute, Gabija; Kvedariene, Violeta (Frontiers in Medicine, 2024)
Background Infertility is a pressing global public health concern, affecting millions worldwide, and the diagnosis of unexplained infertility poses particular challenges. Human seminal plasma allergy, a rarely diagnosed type I hypersensitivity reaction, emerges as a potential but often overlooked contributor to female infertility. With rare reported cases globally, the condition’s low awareness and insufficient differential diagnosis may mask its actual prevalence. Case report This case report presents the clinical case of a 29-year-old woman with unexplained infertility who underwent two unsuccessful IVF procedures and was subsequently diagnosed with human seminal plasma allergy. The patient, known for bronchial asthma and allergic rhinitis exacerbated by inhalant allergens, exhibited eosinophilia and a history of local allergy symptoms (burning sensation, vulvar pruritus, edema, and general discomfort) as well as sneezing and nasal congestion following unprotected intercourse—symptoms compatible with human seminal plasma allergy. Molecular allergy diagnostics revealed pronounced sensitization to dust mites and Can f 5, a canine-specific allergen. A positive skin prick test using her partner’s sperm confirmed the diagnosis of human seminal plasma allergy. The patient’s medical history also includes mild endometriosis, raising questions about the interplay between allergic conditions and fertility. Treatment options such as barrier contraception, antihistamine therapy, and sperm desensitization are discussed. Conclusion Highlighting the need for increased awareness among healthcare professionals, this case emphasizes the significance of reporting and sharing clinical experiences to enhance our understanding of this rare condition. As researchers continue to accumulate relevant information, a more comprehensive understanding of human seminal plasma allergy and its potential impact on female fertility will contribute to improved diagnostic protocols and expanded treatment options. This case report contributes to the growing body of knowledge surrounding this rare allergy, serving as a reminder of possible intricate relationships between allergic conditions and reproductive health.